Book Review- English Trade and Adventure to Russia in the Early Modern Era - Shahid Hussain (Slovo, 2021)
Anglo-Dutch rivalry in the Early Modern Period has received significant scholarly attention, with numerous academics discussing the growing commercial rivalry that eventually culminated in a series of Anglo-Dutch wars in the second half of the seventeenth century. Scholars such as Douglas Irwin, writing in the early 1990s, focused on the growing tensions between the British East India and Dutch East India companies in the subcontinent and South-East Asia, whilst the competition between the two in the Levant and Ottoman Empire has also been well covered by historians including Alastair Hamilton, Alexander Groot and Maurits van den Boogert. In her latest work, English Trade and Adventure to Russia in the Early Modern Era, Maria Salomon Arel masterfully shifts the theatre of the rivalry to Russia. Her focus on Muscovy as a centre of Anglo-Dutch tension is refreshing, particularly given merchants involved in the Muscovy Company were also active members of other trading companies, including the Levant and East India companies.